2011
DOI: 10.1373/clinchem.2010.156976
|View full text |Cite
|
Sign up to set email alerts
|

Building Multidimensional Biomarker Views of Type 2 Diabetes on the Basis of Protein Microheterogeneity

Abstract: BACKGROUND In 2008, the US Food and Drug Administration (FDA) issued a Guidance for Industry statement formally recognizing (during drug development) the conjoined nature of type 2 diabetes (T2D) and cardiovascular disease (CVD), which has precipitated an urgent need for panels of markers (and means of analysis) that are able to differentiate subtypes of CVD in the context of T2D. Here, we explore the possibility of creating such panels using the working hypothesis that proteins, in addition to carrying time-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Since 1995, our group has published extensively on MSIA including core technology conception and development [47], assay development for dozens of human proteins [85,86,87,88], novel data modeling approaches [89], and also demonstrated ultra-high throughput application for >1000 samples per day intended for clinical use [52]. Listed in Table 1 are mass spectrometric immunoassays for human proteins expressing various proteoforms.…”
Section: Mass Spectrometry Immunoassay For Clinically Significant mentioning
confidence: 99%
“…Since 1995, our group has published extensively on MSIA including core technology conception and development [47], assay development for dozens of human proteins [85,86,87,88], novel data modeling approaches [89], and also demonstrated ultra-high throughput application for >1000 samples per day intended for clinical use [52]. Listed in Table 1 are mass spectrometric immunoassays for human proteins expressing various proteoforms.…”
Section: Mass Spectrometry Immunoassay For Clinically Significant mentioning
confidence: 99%
“…Therefore, there is a signif- icant interest in understanding the mechanisms contributing to the development of this condition [154]. Borges et al using a top-down proteomics approach identified a panel of PTM-based biomarkers to distinguish the spectrum of cardio vascular disease (CVD) and T2D co-morbidities [155].…”
Section: Tdp In Biomedical Researchmentioning
confidence: 99%
“…Top row: a) pre-purified Human Serum Amyloid P (contains only one complex-type N-linked glycan 46–47 ), b) pre-purified Bovine Ribonuclease B (RNase B, contains only one high mannose N-linked glycan 48–49 ). Bottom row: c) pre-purified Human Vitamin D Binding Protein (DBP, contains a NeuNAc2-3Gal1-3GalNAc O-linked glycan and no N-linked glycans 50–51 ) d) Pre-purified neutral glycosphingolipids from human granulocytes (largely characterized by their lactose (Gal1-4Glc)-base, 3-Gal and 4-GlcNAc-containing structures). Extracted ion chromatograms and symbol legend in this Figure are the same as in Fig.…”
Section: Figurementioning
confidence: 99%